FINITE ELEMENT ANALYSIS OF ADHESIVELY BONDED TONGUE AND GROOVE GEOMETRY OF THICK COMPOSITE STRUCTURES - Uslu, Mine (INT INST INFORMATICS & SYSTEMICS, 2011)
This study focuses on investigating of parameters which effect the bonding and strength on thick composite sandwich structure models. The joint model is consisting of thick woven E-glass/vinyl ester laminates joined together with tongue and groove geometry. A finite element analysis was used to calculate the shear and peeling stresses generated by longitudinal tensile loads, analysis incorporating the adhesive behavior was performed to accurately estimate the mechanical stresses in the adhesive. The joint strength was estimated by three criteria, tongue length, pre-stress and using different tongue made of steel/aluminum, composite. The distributions of shear and peeling stresses were investigated for various critical ranges. Finite element analysis further confirms that longitudinal tensile loads were applied to the joints, resulting in large concentrated shear and peel stresses near the free edges of bondlines and also stresses values was compared in critic zone for obtain the failure behavior in adhesively joined geometry. The effect of applying the transverse pre-stress on joint strength was also taken into consideration. The results indicate that joint strength increases significantly by applying the transverse pre-stress and it can reverse the sign of the peel stress in the adhesive layer. The joint strength can be significantly improved by selecting appropriate the design parameter values and by using the finite element model, failure behaviors with distributions of stress can be defined obviously.
Keywords: thick composites; sandwich structures; adhesive bonding; design tensile strength; tongue and groove geometry; finite element analysis; JOINTS; STRENGTH; Computer Science